Malaysian urbanization transition: from nascent, pseudo to livable mega - urban region - Abdul Samad Hadi,; Shaharudin Idrus,; Abdul Hadi Harman Shah,; Ahmad Fariz Mohamed, (Environmental Management Society, Malaysia, 2010)
In the relatively short history of modern Malaysian urbanization experiences, a three phase urbanization transition is proposed, namely the phases of nascent, pseudo and the rise of the mega urban region. It is recognized that modern urban centres in the country were founded by the British administration of the country as from the 18th century, albeit the existence of the Melaka empire around the 15th or 13th century. The urban centres founded by the British were mainly administrative centres to administer law and order in order to sustain the exploitation of tin and the vibrancy of commercial rubber production, in addition to the provision of goods and services. These urban centres were generally ‘foreign’ to the conception of life of the local people who participated marginally in the market economy controlled by British capitals and later Chinese migrants’ capital. The required labour force to run these urban centres was met mainly by Chinese and Indian migrants whom the British encouraged to be brought in. Briefly, the basic characterization of the urbanization process during the nascent phase is that the process involved cross border labour flows from South China and India, and the urban centres were just islands of modernisation seeds in the relatively rural spatial domain. The challenge of urban living in the mega urban region centres on sustaining the quality of urban life, access to better quality jobs, shelters, education, personal safety, health and infrastructures in a globalizing world